GENETIC ANALYSIS OF STOMATAL FEATURES OF SOME BREAD WHEAT CULTIVARS UNDER DIFFERENT WATER REGIMES - M. H. Romena; E. Farshadfar (Journal of Animal and Plant Sciences, 2019)
Eight diverse wheat genotypes were selected and crossed in all possible combinations to study the inheritance pattern of stomatal related characters under three different irrigation regimes. Knowledge of the stomata responses to different plant water status is necessary for the breeding varieties with more water use efficiency and drought tolerance. Eight bread wheat genotypes as parents and their 28 F1 hybrids were grown using a completely randomized design (CRD) with four replicates at the greenhouse under different water regimes. The stomatal parameters were assessed on both abaxial (lower) and adaxial (upper) leaf surfaces using a light microscope. The stomatal indices i.e. the operating stomatal conductance to water vapor (gs), the stomatal shape coefficient (SSC) and the potential conductance index (PCI) were estimated using obtained stomatal morphological data. All data were analyzed by both the Griffing and the Hayman diallel methods. Estimates of the genetic components of variation and other genetic parameters indicated that both additive and dominance effects were involved in genetic control of stomatal density and operating stomatal conductance (gs) under different irrigation regime. The results revealed the sensitivity of both kinds of gene effects to the environmental variations. Moderately high estimates of heritability were recorded. Due to summary of all morpho-anatomical traits,theSivand and the Parsi varieties and the Marvdasht×Sivand and the Parsi×Pishtase crosses at normal irrigation regime, the Parsi and Pishtasevarieties and the Marvdasht×Sivand and the Parsi×Pishtase crosses at stress site and the Sirvan variety and the Sivand×Sirvan and Marvdasht×Sirvan crosses at water holding site are the best varieties and crosses for improvement of stomata related characters among other varieties and crosses. Advanced-generation breeding methodswere suggested for improvements of stomata related characters under different water regimes.
Keywords: Combining ability; Diallel analysis; Gas exchange; potential conductance index